2009
DOI: 10.4103/0377-4929.56119
|View full text |Cite
|
Sign up to set email alerts
|

Foregut cystic developmental malformation: New taxonomy and classification - Unifying embryopathological concepts

Abstract: Foregut cystic developmental malformations are rare developmental anomalies. The problems inherent to these malformations are their presentation across specialties that include embryology, anatomy, pathology, thoracic foregut surgery, pediatric surgery and general abdominal surgery. The direct consequence of this variation has resulted in diverse terminology, classification and a failure to identify the correlation. The article aims to summarize and unify the embryological concepts of foregut cystic malformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 0 publications
1
40
0
1
Order By: Relevance
“…Out of these, only the last four contain muscle in their walls and are lined by ciliated epithelium [1, 3]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of these, only the last four contain muscle in their walls and are lined by ciliated epithelium [1, 3]. …”
Section: Discussionmentioning
confidence: 99%
“…These can migrate to different regions of the body. Only few cases outside the posterior mediastinum, which is the most common location, have been reported [1]. Four cases of abdominal, one in the testis, and one in the dorsal scapular region are described in literature [1, 2, 4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, cysts of foregut origin have been classified into bronchogenic cyst, esophageal duplication cyst, and enteric cyst. While newer classification schemes have been proposed to address problems with this historical nomenclature, they are beyond the scope of this review [11].…”
Section: Foregut Cystic Developmental Malformationmentioning
confidence: 99%
“…Duplications may occur anywhere from the mouth to the anus and are believed to have a similar embryologic origin [1]. In 1937, Ladd and Gross [2] suggested that the criteria for a duplication area structure(s) attached or adhered to some part of the alimentary tract and is lined by mucous membrane similar to that part of the alimentary tract and possesses an outer smooth muscle coat.…”
mentioning
confidence: 99%